Beyond Medicine: A Comparative Study on Therapeutic Education and Islamic Spiritual Care in Patient Recovery - Hidayat, Taufik (UIN Antasari Banjarmasin, 2023)
The research discussed in the input highlights the importance of addressing the psychological and emotional well-being of patients in addition to their physical symptoms. Two approaches, therapeutic education interventions and Islamic spiritual care, were examined to enhance the recovery process for patients in hospitals. Therapeutic education interventions focus on providing patients with the knowledge and skills to manage their condition and promote self-care, while Islamic spiritual care incorporates religious and spiritual practices to support patients in coping with their illness and finding meaning in their recovery journey. The study employed an experimental method with an Independent Sample U-test design to compare the average difference in healing motivation between patients receiving therapeutic education intervention and those receiving Islamic spiritual care intervention. The results showed that there was no significant difference in healing motivation between the two groups, suggesting that both intervention methods are equally effective in enhancing healing motivation. The findings have implications for healthcare providers in improving the overall quality of care provided in hospitals. Therapeutic education and Islamic spiritual care can be chosen as intervention methods to support patients' healing motivation and enhance their recovery process.